PHYSICO-CHEMICAL STUDY OF CEMENT DEGRADATION IN THE PRESENCE OF CO2 - SAUKI, ARINA (2012)
The Portland cement has several well-known deficiencies when used at a temperature above 110°C and are due to the formation of α-C2SH being a much denser and stiffen forms thereby leading to cement shrinkage and loss of compressive strength. Even worst, in the presence of high concentrated CO2 underground, cement will degrade. This study is an attempt to investigate on the performance of physicochemical cement degradation by CO2 under variation temperature, pressure and time. The reactivity of neat Class G cement in wet supercritical CO2 and CO2-saturated brine is also compared. Then, the potential additives are selected to design a high CO2 resistance cement which is applicable to be used in high temperature well application. The proposed cement additives are silica fume, fillite cenosphere and sika superplasticizer.